Safety and belonging : constructing a sense of belonging amongst young, middle-class, South African feminine bodies within an 'unsafe' place - Chadwick, Rachelle Dr (University of Pretoria, 2024)
Dissertation (MA (Sociology))--University of Pretoria, 2023.